(untitled) (Journal of Parents and Teachers, 1996)
The text addresses the importance of education and decision making in parenting, emphasizing the need to seek advice from people with good will and perspective. It highlights the relevance of diagnosing situations before applying solutions, avoiding blind and unfounded actions. The central idea is to mature the process of understanding and applying knowledge in education.